MULTICULTURAL TEACHING: CRITICAL-REFLECTIVE APPROACHES - Piper, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1988)
There has been a growing recognition of the need for teachers to examine and to come to greater understanding about multicultural policies in Canada. What is less clear, however, is the kind of approach which best facilitates multicultural awareness. It is argued that Critical Pedagogy (as developed by Giroux, following Freire) provides a promising new framework for the consideration of multicultural ideology and for comparison between this and alternatives such as the anti-racist ideology being currently promoted within the British educational system. It is concluded that the processes of critical reflection are crucial to greater understanding of multiculturalist ideology, in the context of which multiethnic education in Canada is currently being developed. RÉSUMÉ On admet de plus en plus la nécessité pour les professeurs d'étudier et d'approfondir les politiques multiculturelles du Canada. Ce qui est moins clair, par contre, c'est le type de démarches qui favorisent la prise de conscience multiculturelle. Les auteurs soutiennent que la pédagogie critique (telle que développée par Giroux, à la suite de Freire) offre un nouveau schéma prometteur pour l'étude de l'idéologie multiculturelle et pour sa comparaison aux autres options telles que l'idéologie anti-raciste que prone actuellement le système d'enseignement britannique. L'auteur conclut que les processus de réflexion critique sont cruciaux si l'on veut parvenir à une meilleure compréhension de l'idéologie multiculturelle dont s'inspire actuellement le développement de renseignement multi-ethnique au Canada.